Factors Influencing Land Utilization Among Poor Rural Household in Kedah, Malaysia - Bakar, Mohd Azmeer Abu; Rahim, Asyirah Abdul (European Publisher, 2019)
The land resources are part of the natural assets that provide direct and indirect benefits to people, especially the rural poor. In poverty studies, utilization and management of the land are important to the livelihood of poor people, particularly in supplying food and generating income. Several factors influence the utilization of the land in their surrounding among rural poor household and the factors of influence in land utilization are also different when time and space are different. Therefore, these objectives are to determine the factors of influence in land utilization among poor rural households and analyse the relationships between land utilization and yield. The questionnaire survey was adopted, and 124 respondents were selected based on snowball sampling in Jerlun, Kedah. In this study, there are five main factors, namely are the social economy, spatial, physical, temporal and risk. Then, those factors which include seven variables will be analysed in multiple regression; are social interaction, level of technology, infrastructure, transportation, market accessing, season, and climate change. Based on multiple regression analysis, utilization factors are significant for social interaction, transportation and climate change. Final thought, the type of social interaction, mode of transportation and impact climate change to activity has influenced the poor rural household to utilize the land resources for their life survive.